Standardization of Counselor Services in Dealing with Student Problems in the Global Era - Choli Astutik; Mafruhah mafruhah; Yulie Marta Aulina (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to determine the service standards of school counselors in helping students' problems in the global era, with a focus on counselor standards in the field of counselor competence and academic qualifications. This research is a qualitative research that reveals field findings by describing in depth the data obtained in the field. The data collection methods used in this study were interviews, observations, and documentation. The results showed that school counselors at Madrasah Aliyah Raudhatut Thalibin had not fully met the counselor competency standards and academic qualifications described by the national education department. This imperfection occurs because school counselors have not collaborated with other professional experts such as psychologists and psychiatrists in dealing with problems experienced by students and they do not have a formal educational background, namely professional counselor education. The implementation of services by school counselors to students has been going well and quite innovative in keeping up with the times.